If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5(x + -2) + -1(0.3x + -16) = 0 Reorder the terms: 0.5(-2 + x) + -1(0.3x + -16) = 0 (-2 * 0.5 + x * 0.5) + -1(0.3x + -16) = 0 (-1 + 0.5x) + -1(0.3x + -16) = 0 Reorder the terms: -1 + 0.5x + -1(-16 + 0.3x) = 0 -1 + 0.5x + (-16 * -1 + 0.3x * -1) = 0 -1 + 0.5x + (16 + -0.3x) = 0 Reorder the terms: -1 + 16 + 0.5x + -0.3x = 0 Combine like terms: -1 + 16 = 15 15 + 0.5x + -0.3x = 0 Combine like terms: 0.5x + -0.3x = 0.2x 15 + 0.2x = 0 Solving 15 + 0.2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 0.2x = 0 + -15 Combine like terms: 15 + -15 = 0 0 + 0.2x = 0 + -15 0.2x = 0 + -15 Combine like terms: 0 + -15 = -15 0.2x = -15 Divide each side by '0.2'. x = -75 Simplifying x = -75
| (D^3+3D^2-4D)y=0 | | v^2-7v+11=0 | | 3y-y+4y=12 | | 6(z+2)-2(2z+5)= | | 121x^2-154x+49=0 | | 12x+2(x-3)=5(2x-1)+7 | | 5x-6=-4(3-x) | | 225x^2-81=0 | | 225x^2-81=0 | | 2x+15=3-x | | u^2+9u-3=0 | | 5h+2(11-h)-5= | | 4(4y-1)+3-2(3+y)=0 | | -3(4-6y)+7(-y+5)=-8 | | (a+6)(a*2-8a+8)= | | 6c^2+7cd-5d^2= | | 2(x+3)-3x=5-x+1 | | 2x+5+6x-20=180 | | 8x-2(x+5)=5(2x-6) | | 9x-3y=27 | | 6a-47-2a=8a-15 | | 6x-5=-2x+11 | | 3(x+4)-2(x-1)=4(x+4) | | 75-3n+6n=12+15n-2+3n+20 | | -5+3m=3-m | | -3(-2)+6+-2= | | -1+3(x-1)=8x-5(x-2)-14 | | 7x-40-27x=10x+6+36 | | x^2+18x+53=594 | | x^2-5x-11x=0 | | 9x-7=4x+1 | | 9d-4=49 |